ANALISIS POTENSI PENERIMAAN RETRIBUSI (Studi Pada Rumah Sakit Umum Daerah (RSUD) Kabupaten Buton) - Sakina Linsani; Zainuddin Saenong; Rosnawintang (Bajang Institute, 2022)
This study aims to determine the amount of potential health service retribution received by Buton District Hospital, 2017-2018 period. The data used are secondary data sourced from the Buton District Hospital. The scope of the researcher is health services as seen from the aspects of the facilities and services in the RSUD. To analyze the acceptance of retribution using descriptive statistical analysis. Based on the results of the research analysis, the potential for receiving health service levies at the Buton District Hospital from 2017-2018 has different potentials, with fluctuating retribution receipts. The largest receipts of user fees are for Pharmacy and Pharmacy services, while the receiving of the lowest fees is for the Hospital Blood Transfusion Unit (UTD RS). In receiving retribution depending on how many visits to the RSUD.